The range and suitability of outcome measures used in the assessment of palliative treatment for inoperable malignant bowel obstruction: A systematic review. (October 2022) - Bravington, Alison; Obita, George; Baddeley, Elin; Johnson, Miriam J; Murtagh, Fliss EM; Currow, David C; Boland, Elaine G; Nelson, Annmarie; Seddon, Kathy; Oliver, Alfred; Noble, Simon IR; Boland, Jason W
Background: Malignant bowel obstruction, a complication of certain advanced cancers, causes severe symptoms which profoundly affect quality of life. Clinical management remains complex, and outcome assessment is inconsistent. Aim: To identify outcomes evaluating palliative treatment for inoperable malignant bowel obstruction, as part of a four-phase study developing a core outcome set. Design: The review is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA); PROSPERO (ID: CRD42019150648). Eligible studies included at least one subgroup with obstruction below the ligament of Treitz undergoing palliative treatment for inoperable malignant bowel obstruction. Study quality was not assessed because the review does not evaluate efficacy. Data sources: Medline, Embase, the Cochrane Database, CINAHL, PSYCinfo Caresearch, Open Grey and BASE were searched for trials and observational studies in October 2021. Results: A total of 4769 studies were screened, 290 full texts retrieved and 80 (13, 898 participants) included in a narrative synthesis; 343 outcomes were extracted verbatim and pooled into 90 unique terms across six domains: physiological, nutrition, life impact, resource use, mortality and survival. Prevalent outcomes included adverse events (78% of studies), survival (54%), symptom control (39%) and mortality (31%). Key individual symptoms assessed were vomiting (41% of studies), nausea (34%) and pain (33%); 19% of studies assessed quality of life. Conclusions: Assessment focuses on survival, complications and overall symptom control. There is a need for definitions of treatment 'success' that are meaningful to patients, a more consistent approach to symptom assessment, and greater consideration of how to measure wellbeing in this population.